2022
DOI: 10.3389/fmicb.2022.827863
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Microbiome of the Sponge Mycale (Oxymycale) acerata in the Western Antarctic Peninsula

Abstract: The sponge microbiome, especially in Low Microbial Abundance (LMA) species, is expected to be influenced by the local environment; however, contrasting results exist with evidence showing that host specificity is also important, hence suggesting that the microbiome is influenced by host-specific and environmental factors. Despite sponges being important members of Southern Ocean benthic communities, their relationships with the microbial communities they host remain poorly studied. Here, we studied the spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 64 publications
5
8
0
Order By: Relevance
“…A total of 88 specimens belonging to four demosponge species living in similar shallow rocky benthic environments were collected at three regions representative of polar, temperate, and tropical coastal environments. Mycale acerata (LMA) (Sacristań-Soriano et al, 2020;Happel et al, 2022) and Dendrilla antarctica (LMA) (Koutsouveli et al, 2018;Dıéz-Vives et al, 2020), common yellow sponges in hard bottom benthic environments from polar (Antarctic) waters; and Agelas oroides (HMA) (Vacelet and Donadey, 1977;Blanquer et al, 2013), a lobed orange sponge present in temperate (Mediterranean Sea and Eastern Atlantic) waters; and Acanthella cavernosa (LMA) (Coelho et al, 2018;Cleary et al, 2019), a red spiky sponge present in tropical (Pacific Ocean) waters. Both Antarctic sponges, M. acerata (n=28) and D. antarctica (n=28) were collected at four different stations on Deception and Livingston Islands (South Shetland Islands) (Figure 1 and Table 1).…”
Section: Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 88 specimens belonging to four demosponge species living in similar shallow rocky benthic environments were collected at three regions representative of polar, temperate, and tropical coastal environments. Mycale acerata (LMA) (Sacristań-Soriano et al, 2020;Happel et al, 2022) and Dendrilla antarctica (LMA) (Koutsouveli et al, 2018;Dıéz-Vives et al, 2020), common yellow sponges in hard bottom benthic environments from polar (Antarctic) waters; and Agelas oroides (HMA) (Vacelet and Donadey, 1977;Blanquer et al, 2013), a lobed orange sponge present in temperate (Mediterranean Sea and Eastern Atlantic) waters; and Acanthella cavernosa (LMA) (Coelho et al, 2018;Cleary et al, 2019), a red spiky sponge present in tropical (Pacific Ocean) waters. Both Antarctic sponges, M. acerata (n=28) and D. antarctica (n=28) were collected at four different stations on Deception and Livingston Islands (South Shetland Islands) (Figure 1 and Table 1).…”
Section: Sample Collectionmentioning
confidence: 99%
“…This is reflected in "The sponge microbiome project" (Moitinho-Silva et al, 2017a), where the microbiomes of 268 temperate and tropical sponge species were analyzed, but no polar species were included. However, in recent years, the microbiota of 31 Antarctic sponge species (or probably less since some of them were only identified to genus level) have been studied using 16S rRNA amplicon sequencing analysis (Webster et al, 2004;Rodrıǵuez-Marconi et al, 2015;Caŕdenas et al, 2018;Caŕdenas et al, 2019;Lo Giudice et al, 2019;Steinert et al, 2019;Dıéz-Vives et al, 2020;Moreno-Pino et al, 2020;Papale et al, 2020;Sacristań-Soriano et al, 2020;Ruocco et al, 2021;Cristi et al, 2022;Happel et al, 2022). This is still a very small amount, considering that the most recent estimates of sponge species richness in the Southern Ocean and neighboring oceanographic regions were of 400 species as published in the Biogeographic Atlas of the Southern Ocean (Janussen and Downey, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Culture-independent methods have been applied to different sponge species to investigate the whole community, collected all around Antarctica, at sites in McMurdo Sound and Terra Nova Bay (Ross Sea, Antarctica), Antarctic Peninsula, South Shetland Islands, and Palmer Archipelago (e.g., [ 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ]). Webster et al [ 135 ] first studied Antarctic-sponge-associated prokaryotic communities.…”
Section: Invertebrates From Extreme Benthic Habitats As Hosts Of Micr...mentioning
confidence: 99%
“…Rodríguez-Marconi et al [ 136 ] highlighted that Antarctic-sponge-associated microbial communities differed at the phylum level from those known for temperate and tropical ecosystems. The assessment of host-specificity was the main aim of recent works by Cárdenas et al [ 138 ], Sacristán-Soriano [ 142 ], and Happel et al [ 143 ], who found a high similarity among the microbiota of cold-water sponge species collected from different Antarctic sites. Cristi et al [ 145 ] reported a high degree of specificity of bacterial symbiotic community in Hymeniacidon torquata , suggesting reduced presence of transient bacteria.…”
Section: Invertebrates From Extreme Benthic Habitats As Hosts Of Micr...mentioning
confidence: 99%